Funciones desempeñadas en Cobranzas & Courier Con.tacto S.A.C - Lesama Alvarez, Janice Nohely (2019)
The economic growth achieved by the Peruvian economy in the last decade and the good business environment have led companies to become contractors of other company’s services, in order to supply labor demand. Such is the case of Rena Ware del Peru S. A., a company with over 52 years in the market needs to be supplied with labor in various areas, such as sales, collections, credits, etc. Cobranzas & Courier Con.tacto S.A.C., has been providing Rena Ware of these services for more than 5 years and each time it continues expanding the offered services. Below is a detailed description of the company regarding its historical review, vision, mission, organizational chart, among others, which will allow us to know about it and the positions occupied within it. Reference is also made to each of the functions performed within the organization during labor management, as well as the problems and solutions found for them. Finally, an appreciation of the professional training obtained during the years is made as part of the students of the professional school of Administration.